2009
DOI: 10.4049/jimmunol.0803743
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role for Protease-Activated Receptor-2 against Influenza Virus Pathogenesis via an IFN-γ-Dependent Pathway

Abstract: Protease-activated receptor-2 (PAR2), a receptor highly expressed in the respiratory tract, can influence inflammation at mucosal surfaces. Although the effects of PAR2 in the innate immune response to bacterial infection have been documented, knowledge of its role in the context of viral infection is lacking. We thus investigated the role of PAR2 in influenza pathogenesis in vitro and in vivo. In vitro, stimulation of PAR2 on epithelial cells inhibited influenza virus type A (IAV) replication through the prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 54 publications
(53 reference statements)
3
56
3
Order By: Relevance
“…40,42,45 These results suggested that PAR2ko mice would be protected from IAV infection because they would express higher levels of IFN-b. Indeed, the Vogel group found that PAR2ko mice For personal use only.…”
Section: Role Of Par2 In Iav Infection In Micementioning
confidence: 68%
See 3 more Smart Citations
“…40,42,45 These results suggested that PAR2ko mice would be protected from IAV infection because they would express higher levels of IFN-b. Indeed, the Vogel group found that PAR2ko mice For personal use only.…”
Section: Role Of Par2 In Iav Infection In Micementioning
confidence: 68%
“…40 Similarly, the Riteau group found that PAR2 activation suppressed CCL5 expression by A549 human epithelial cells after influenza A infection. 45 We found that murine embryonic CFs lacking PAR2 expressed higher levels of IFN-b and CCL5 expression after poly I:C stimulation compared with wild-type (WT) fibroblasts (Figure 4). 42 Taken together, these results indicate that PAR2 suppresses For personal use only.…”
Section: Par2 Modulation Of Tlr2 Tlr3 and Tlr4 Signaling In Epithelmentioning
confidence: 94%
See 2 more Smart Citations
“…[109][110][111] Three major pathways are implicated in complement activation: classical, lectin and alternative pathways, as shown in figure 1.3. The classical and alternative pathways converged at C3, with two C3 convertases cleaving C3 to produce anaphylatoxin C3a and opsonin C3b, then C5 convertases cleaving C5…”
Section: Human Complement System and C3a Receptormentioning
confidence: 99%